Rental car online system - Mohd Khalid, Mohd Sapuan (2012)
Nowadays,there are online car reservations which give much benefit to user.A rental service is a service in which customers arrive to request the hire of a rental unit.It is more convenient than carrying the cost of owning and maintaining the unit.In Universiti Malaysia Pahang,there is also having a rental services which is the system is work manually and individually.There were several problems occur on student,which is student always got spam in memo system in UMP e-community portal regarding the advertisement of rental car.Moreover,the difficulties to find a rental car for student who want to rent a transport and the problems with publish an advertisement about rental car in liMP.The solution has been come out on solving the various problems that always occur on students.A web application is an application that is accessed over a network such as the Internet or an intranet.Therefore with this new method,the process will be more efficient and the safety of hiring car is secure.It's also the best way to increase the quality of management and can reduce the time constraints.